High titers of neutralizing antibodies in the blood fail to eliminate SARS‐CoV‐2 viral RNA in the upper respiratory tract. Issue 1 (20th October 2022) - Li, Lu; Cui, Jianping; Tang, Jingyan; Shi, Jingrong; Deng, Xilong; Zheng, Xiaowen; Fan, Qinghong; Liu, Ying; Yu, Haisheng; Tang, Xiaoping; Hu, Fengyu; Li, Feng
Abstract: Retest‐positive severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) viral RNA, as a unique phenomenon among discharged individuals, has been demonstrated to be safe in the community. Still, the underlying mechanism of viral lingering is less investigated. In this study, first, we find that the frequency of viral RNA‐positive retesting differs among variants. Higher ratios of viral RNA‐positive retest were more frequently observed among Delta (61.41%, 514 of 837 cases) and Omicron (39.53%, 119 of 301 cases) infections than among ancestral viral infection (7.27%, 21 of 289 cases). Second, the tissues where viral RNA reoccurred were altered. Delta RNA reoccurred mainly in the upper respiratory tract (90%), but ancestral virus RNA reoccurred mainly in the gastrointestinal tract (71%). Third, vaccination did not reduce the frequency of viral RNA‐positive retests, despite high concentrations of viral‐specific antibodies in the blood. Finally, 37 of 55 (67.27%) Delta‐infected patients receiving neutralizing antibody therapy become viral RNA retest positive when high concentrations of neutralizing antibodies still patrol in the blood. Altogether, our findings suggest that the presentence of high titers of neutralizing antibodies in the blood is incompetent in clearing residual viral RNA in the upper respiratory tract.